METTL3 promotes the osteogenic differentiation of periosteum-derived MSCs via regulation of the HOXD8/ITGA5 axis in congenital pseudarthrosis - Weihua Ye; Zheng Liu; Yaoxi Liu; Han Xiao; Qian Tan; An Yan; Guanghui Zhu (Regenerative Therapy)
Background: Congenital pseudarthrosis of the tibia (CPT) is a dominant health challenge in pediatric orthopedics. The essential process in the development of CPT is the limited capacity of mesenchymal stem cells (MSCs) derived from CPT to undergo osteogenic differentiation. Our research aimed to elucidate the role and mechanism of methyltransferase-like 3 (METTL3) in the osteogenic differentiation process of CPT MSCs. Methods: The osteogenic differentiation medium was used to culture MSCs, and the detection of osteogenic differentiation was performed using Alizarin Red S and alkaline phosphatase (ALP) assays. Gene or protein expression was assessed by quantitative real-time polymerase chain reaction (qRT-PCR), Western blot, or immunofluorescence (IF) staining. The m6A modification of Homeobox D8 (HOXD8) was verified by methylated RNA immunoprecipitation (MeRIP) assay. Interactions between METTL3 and HOXD8 or HOXD8 and integrin alpha 5 (ITGA5) promoter were validated by the luciferase reporter gene, RIP, and chromatin immunoprecipitation (ChIP) assays. Results: METTL3 overexpression enhanced CPT MSCs' osteogenic differentiation. METTL3 stabilized the HOXD8 in an m6A-dependent manner. Moreover, the overexpressed ITGA5 up-regulated the CPT MSCs’ osteogenic differentiation. Further, HOXD8 could transcriptionally activate ITGA5. METTL3 increased the transcription of ITGA5 via HOXD8 to enhance the osteogenic differentiation of CPT MSCs. Conclusion: METTL3 promoted osteogenic differentiation via modulating the HOXD8/ITGA5 axis in CPT MSCs.